2005
DOI: 10.1080/13651820510028800
|View full text |Cite
|
Sign up to set email alerts
|

Diminished gallbladder motility in rotund leptin‐resistant obese mice

Abstract: These data suggest that leptin-resistant Rotund mice have (1) enlarged gallbladders with (2) diminished contractility compared to lean control mice. Therefore, this study confirms that leptin-resistance is associated with abnormal biliary motility and may lead to gallstone formation in leptin-resistant obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Previous studies from our laboratory have demonstrated that Lep ob and Lep db mice have hyperglycemia, insulin-resistance, hyperinsulinemia, hyperlipidemia, enlarged gallbladders, and reduced response of their gallbladder smooth muscle to neurotransmitters such as ACh, NPY, and CCK. [6][7][8][9]21,22 The serum glucose, insulin, cholesterol, and triglycerides in these mice correlated inversely with their in vitro gallbladder responses. 6 We have also shown that the lipids in the gallbladder wall of lean (C57BL/6J) and obese (Lep ob ) mice correlate with the impaired in vitro gallbladder response to neurotransmitters.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies from our laboratory have demonstrated that Lep ob and Lep db mice have hyperglycemia, insulin-resistance, hyperinsulinemia, hyperlipidemia, enlarged gallbladders, and reduced response of their gallbladder smooth muscle to neurotransmitters such as ACh, NPY, and CCK. [6][7][8][9]21,22 The serum glucose, insulin, cholesterol, and triglycerides in these mice correlated inversely with their in vitro gallbladder responses. 6 We have also shown that the lipids in the gallbladder wall of lean (C57BL/6J) and obese (Lep ob ) mice correlate with the impaired in vitro gallbladder response to neurotransmitters.…”
Section: Discussionmentioning
confidence: 91%
“…[3][4][5] Recent animal and human data from our laboratory suggest that insulin resistance is associated with increased gallbladder volume and/or impaired gallbladder emptying. [6][7][8][9][10] In addition, gallbladders of diabetic patients have been shown to be enlarged with decreased emptying in response to a meal. 3,11 Resistin is a member of a family of resistin-like molecules (RELMs), which were earlier discovered as the FIZZ gene family.…”
Section: Introductionmentioning
confidence: 98%
“…Gallbladder stones are one of the most common surgical diseases affecting the world population, chiefly because its risk factors such as obesity are very common in modern society [1]. The open cholecystectomy technique was first per− formed late in the nineteenth century [2] and de− veloped in the twentieth century as described by O'Conor in 1922 [3].…”
mentioning
confidence: 99%